A newly identified photosystem II Subunit P gene TaPsbP4A-1 in Triticeae species negatively regulates wheat powdery mildew resistance - Xu, Jun; Wang, Mengfei; Ren, Yueming; Luo, Wanglong; Zhang, Lu; Liu, Shuangwei; Hu, Ping (Frontiers in Plant Science, 2024)
The photosystem II (PSII) Subunit P (PsbP) protein is a component of its oxygenevolving complex, which can oxidize water to produce oxygen using light energy and is critical to the core components and stability of PSII. Using the whole-genome information, the PsbP genes of 10 plant species were comprehensively identified. The expression patterns of wheat PsbPs under Blumeria graminis f. sp. tritici (Bgt) infection were assessed using qRT-PCR, and the functions of TaPsbPs in wheat powdery mildew resistance were studied using barley stripe mosaic virus-induced gene silencing. In total, 122 PsbP genes were divided into 8 classes with similar gene structures. No tandem repeat events were identified in wheat PsbP, suggesting that the PsbP genes in common wheat were donated by its diploid progenitor species. The expression levels of TaPsbP2A-1, TaPsbP3A-1, TaPsbP4A-1, TaPsbP4A-2, and TaPsbP7A-2 were induced by Bgt. The silencing of TaPsbP4A-1 increased the resistance of common wheat 'Bainong AK58' to Bgt. This study provides valuable information for functional and evolutionary research on the PsbP gene family.